Analysis of the impact of the use of Artificial Intelligence as a service for the detection of unprotected facial passers-by - Vera Cuya, Ronald Martín (2023)
21 st LACCEI International Multi-Conference for Engineering, Education, and Technology & 4th CLADI-CONFEDI: “Leadership in Education and Innovation in Engineering in the Framework of Global Transformations: Integration and Alliances for Integral Development”, Hybrid Event, Buenos Aires - Argentina, July 17 - 21, 2023.